Evaluating the impact of an online educational program – STOPIPV – for Cypriot midwives in intimate partner violence in pregnancy: a pre-post study - Hadjigeorgiou, Eleni; Manoli, Emmanouela; Kouta, Christiana; Karanikola, Maria; Middleton, Nicos (My University, 2024)
Background: Intimate partner violence (IPV) is a major public health issue affecting women. The period of pregnancy does not appear to be a protective factor. Exposure to intimate partner violence is associated with negative outcomes for maternal and infant health. Consequently, midwives face challenges in the assessment, detection, and referral of incidents of intimate violence in pregnancy. Aim: To evaluate the impact of an online educational program, “STOP IPV” on the knowledge, attitudes, and preparedness of Cypriot midwives to conduct routine inquiries about IPV; and to assess the impact of the workplace on conducting routine inquiries about IPV with women during pregnancy. Method: A total of 171 out of the 348 registered midwives in Cyprus participated in the online educational program. Out of these 103 completed in full the pre-post questionnaire which measured the knowledge, preparedness, and perceptions of workplace organizational barriers to routine enquiry, as well as the anticipated impact of training on their practice. Data were then analysed using SPSS software version 25 using descriptive and inferential statistics. Result: The majority of participants, 33.9%, reported not having received any previous training on IPV during pregnancy. Regarding obstacles to conducting IPV, midwives reported that the presence of the partner during visits greatly affected them, with 60.2% (n=62) expressing this sentiment. Language barriers posed similar challenges, with the same percentage indicating difficulty. Additionally, they stated that there was no suitable private space in the health facilities where they worked to inquire about IPV with women, 47.6% (n=49). There was a significant increase in the mean score of preparedness to undertake routine IPV enquiry after intervention (M=9.4, SD=0.79) compared with before the intervention (M=3.33, SD=1.02); t(102)=7.19, p< .001. Conclusion: An online educational program “STOP IPV” for Cypriot midwives has improved knowledge, attitudes, and preparedness to conduct routine inquiries. There is a recognised need in Cyprus to develop clinical guidelines for the management of such incidents in Cyprus, as well as to continue and develop the specific educational program.
Keywords: Midwifery; online educational program